1982
DOI: 10.1111/j.1399-0004.1982.tb00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial reciprocal translocation, t(2;10)(p24;q26), resulting in duplication 2p and deletion 10q

Abstract: We describe a familial reciprocal translocation between the distal part of the short arm of chromosome 2 and the long arm of chromosome 10. Five individuals in two generations had multiple congenital anomalies. Their karyotypes were 46, XX or XY,−10, + der(10), t(2;10)(p24;q26). Seven persons were balanced translocation carriers whose karyotypes were 46, XX or XY, t(2;10)(p24;q26). Common manifestations included mental retardation, strabismus, narrow high‐arched palate, wide alveolar ridges, other facial abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Case 6 (BWIS #2907) represents a patient with an unidentified 1Oq deletion who died suddenly at 20 months of age. Six of 15 similar cases (40%) reviewed had at least one CCVM (Lewandowski et al 1978, Turleau et al 1979, Ray et al 1980, Wegner et al 1981, Larson et al 1982, Davis et al 1982, van de Vooren et al 1984, Shapiro et al 1985b, Holden & MacDonald 1985, Martin 1986). PDA and VSD each occurred in four patients, while five other CCVMs occurred in single patients.…”
Section: Resultsmentioning
confidence: 99%
“…Case 6 (BWIS #2907) represents a patient with an unidentified 1Oq deletion who died suddenly at 20 months of age. Six of 15 similar cases (40%) reviewed had at least one CCVM (Lewandowski et al 1978, Turleau et al 1979, Ray et al 1980, Wegner et al 1981, Larson et al 1982, Davis et al 1982, van de Vooren et al 1984, Shapiro et al 1985b, Holden & MacDonald 1985, Martin 1986). PDA and VSD each occurred in four patients, while five other CCVMs occurred in single patients.…”
Section: Resultsmentioning
confidence: 99%
“…The pedigree of the family is shown in Figure 1 of Larson et al (1982). In the present report the patients and relatives studied will be referred to by the pedigree number.…”
Section: Methodsmentioning
confidence: 99%
“…We assayed these enzymes in the red cells of four patients who had a duplication of the region 2p24-,2pter (Larson et al 1982) due to an unbalanced arrangement of a familial t(2;10)(p24;q26). A dosage effect was demonstrated for ACPl but not MDH1.…”
mentioning
confidence: 99%
“…Although partial trisomy of the short arm of chromosome 2 has been suggested in a few patients during the 1960s, the first two children with this syndrome documented by banding techniques were reported in 1974 (StoU et al 1974). Since then, numerous children with this chromosome aberration have been described (Magenis et al, 1975;Fr^ncke & Jones, 1976;Cassidy et al, 1976;Armendares & Salamanca-Gomez, 1978;Sekhone/a/., 1978;Mayer ^r a/., 1978;Yunise(a/., 1979;Kishi era/., 1980;Nagono, Kano, Kobuchi & Kajitani, 1980;Monteleone et aL, 1981;Larson et al, 1982;Rosenfeld et al, 1982;Fineman et al, 1983;Wakita et al, 1985). In addition, Buyseet al, (1977) reported of a foetus with partial trisomy 2p diagnosed prenatally.…”
Section: Introductionmentioning
confidence: 99%